Enhanced chain packing achieved via putative headgroup ion-triplet formation in binary anionic lipid/cationic surfactant mixed monolayers. (December 2019) - Wölk, Christian; Hause, Gerd; Gutowski, Olof; Harvey, Richard D.; Brezesinski, Gerald
Graphical abstract: Highlights: A simple synthetic model system has been created for studying lipid-lipid interactions in S. aureus membranes. Oppositely charged DPPG and DHDAB are studied by surface-sensitive X-ray scattering and spectroscopy in 2D monolayers. The equimolar mixture gives rise to a neutral interface due to charge compensation (ion-pair formation). The biomimetic DPPG/DHDAB 7/3 mixture forms the most tightly packed condensed phase. A phase diagram has been determined based on thermodynamic and structural data. Abstract: Lipid/surfactant miscibility was investigated in monolayers composed of binary mixtures of dipalmitoylphosphatidylglycerol (DPPG) and dihexadecyldimethylammonium bromide (DHDAB). Langmuir monolayers formed from biomimetic DPPG/DHDAB mixtures based on the anionic:cationic lipid ratios observed in the bacterium Staphylococcus aureus (7:3 and 1:1) were examined alongside those of the pure amphiphiles and a surfactant rich 3:7 mixture. Using a combination of GIXD, TRXF and IRRAS, DPPG/DHDAB 1:1 monolayers were found to form a more stabilised condensed phase compared to pure DPPG, which was composed entirely of electrostatically neutral ion pairs, analogous to the so-called catanionic amphiphiles spontaneously formed by single-chain surfactants with opposing headgroup charges. Despite the lack of lateral charge repulsion the ion paired phase of DPPG/DHDAB exhibited slightly looser chain packing that was observed for DPPG indicating a significant steric effect on packing geometry caused by ion pair formation. Surprisingly, the 7:3 mixture of DPPG/DHDAB formed a completely condensed phase, with no isotherm transitions, in which the chain packing was significantly closer than was found for either DPPG or the totally ion paired monolayer. It is postulated that this mixture forms a distinct DPPG/DHDAB/DPPG ion triplet phase in which the overall negative charge is delocalised across the headgroups. Vesicles composed from the 7:3 mixture formed highly stable dispersions with an increased gel to liquid crystalline phase transition temperature with respect to its pure components. Increasing the proportion of DHDAB above 50 mol% led to demixing between the condensed ion paired phase and the more fluid surfactant, as was clearly observed in epifluorescence images taken of the surface films.